Influence of Celebrity Endorsement towards Beauty Care Products - Santoki, Dr. Ashwinkumar A. (The journal of contemporary issues in business and government, 2022)
Purpose: Celebrity endorsement has developed into a potent marketing tactic that helps businesses set themselves apart from rival brands in the eyes of consumers. The primary goal of this research is to examine how celebrity endorsements affect customer attitudes about beauty care goods. Design/Methodology/Approach: A self-administered questionnaire was completed by 141 female’s respondent and data were being analysed with the help of factor analysis and structured equation modelling using SmartPLS. This study employed a single cross-sectional descriptive research design. Findings: The results revealed that celebrity personality positively affects celebrity credibility, and celebrity credibility favourably affects the elements that influence celebrity endorsement of beauty care products, including product recognition, awareness and recall, positive word of mouth, and changing behaviour. It is also discovered that celebrity credibility has no beneficial effect on product inquiries. Funding Statement: No specific grant was given to this research by any funding organisation in the public, private, or non-profit sectors. Ethical Compliance: The 1964 Helsinki Declaration and its later amendments or comparable ethical standards were followed in all procedures carried out in studies involving human subjects. These procedures also complied with institutional and/or national research committee ethical requirements. Note: This is not a medical research.